The role of RM for DMCs in the run up to the London Olympics 2012 - Nisbet, David (2009)
This dissertation will implement The Process Model of Relationship Marketing (Parvatiyar and Sheth 2000) to analyse existing Relationship Marketing (RM) practices and attempt to compare findings to existing literature and academic best-practice in order to reveal managerial implications for MangoLondon. Research objectives include: • To identify criteria or a model through which to analyse the effectiveness of Relation Marketing practice • To use this model to identify current management of these relationships at MangoLondon • Make suggestions for the MangoLondon in view of the 2012 London Olympics Qualitative interviews were carried out with management at the organisation and compared to interviews with customers and secondary data. This dissertation reveals that MangoLondon effectively manages some aspects of the process model, such as communication and trust with its customers. However, there are shortfalls in current management and governance of RM processes. Based on the findings of this dissertation managerial implications have been suggested which may inform the business plan for MangoLondon in the lead up to the 2012 Olympics in London.